Stakeholders' Opinions on the Implementation of Pediatric Whole Exome Sequencing: Implications for Informed Consent. Issue 4 (12th July 2013) - Levenseller, Brooke L.; Soucier, Danielle J.; Miller, Victoria A.; Harris, Diana; Conway, Laura; Bernhardt, Barbara A.
Abstract: Advances in whole genome and whole exome sequencing (WGS/WES) technologies have led to increased availability in clinical settings. Currently, there are few guidelines relating to the process and content of informed consent for WGS/WES, nor to which results should be returned to families. To address this gap, we conducted focus groups to assess the views of professionals, parents, and adolescents for the future implementation of WES. The discussions assessed understanding of the risks and benefits of WES, preferences for the informed consent discussion, process for return of results, and the decision‐making role of the pediatric patient. Professional focus group participants included bioethicists, physicians, laboratory directors, and genetic counselors. Parent focus groups included individuals with children who could be offered sequencing due to a potential genetic cause of the child's condition. On‐line discussion groups were conducted with adolescents aged 13–17 who had a possible genetic disorder. We identified discrepancies between professionals and patient groups regarding the process and content of informed consent, preference for return of results, and the role of the child in decision‐making. Professional groups were concerned with the uncertainty regarding professional obligations, changing interpretation in genomic medicine, and practical concerns of returning results over time. Parent and adolescent groups focused on patient choice and personal utility of sequencing results. Each group expressed different views on the role of the child in decision‐making and return of results. These discrepancies represent potential barriers to informed consent and a challenge for genetic counselors regarding the involvement of pediatric patients in decision‐making and return of results discussions.